2004
DOI: 10.1677/joe.0.1800311
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II influences ovarian follicle development in the transgenic (mRen-2)27 and Sprague-Dawley rat

Abstract: There is accumulating evidence that local reninangiotensin systems (RASs) influence cell growth and organ function in a variety of tissues including the ovary. The first aim of this study was to characterise the cellular location of RAS components in the rat ovary. This was facilitated by the use of the hypertensive transgenic (mRen-2)27 rat which overexpresses renin and angiotensin in extra-renal tissues. Comparisons were made with normal Sprague-Dawley (SD) rats. The second aim was to determine if the upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…Moreover, infusion of Ang II in rats is also associated with a reduction in antral and preovulatory follicles [46]. Given the increased activity of the reninangiotensin system in obesity [47] and reduced follicular development in ovaries of obese female mice [48], we postulate that higher levels of Ang II could be contributing to the reduction in ovarian follicle development in obese rats.…”
Section: Effect Of Losartan On Reproductive Parametersmentioning
confidence: 89%
“…Moreover, infusion of Ang II in rats is also associated with a reduction in antral and preovulatory follicles [46]. Given the increased activity of the reninangiotensin system in obesity [47] and reduced follicular development in ovaries of obese female mice [48], we postulate that higher levels of Ang II could be contributing to the reduction in ovarian follicle development in obese rats.…”
Section: Effect Of Losartan On Reproductive Parametersmentioning
confidence: 89%
“…Several lines of evidence in rats and rabbits also suggest that AngII alters the fate of the growing follicle, driving it toward atresia; the type 2 receptor occurs on atretic but not healthy granulosa cells (12)(13)(14), receptor binding increased with the induction of granulosa apoptosis in vitro (15), and treatment of granulosa cells with AngII induced DNA fragmentation and decreased estradiol secretion (16,17). This, however, may not be true in other species.…”
mentioning
confidence: 99%
“…In addition, expression of the AT2R gene drastically decreased during the periovulatory period compared with the other periods. A previous study using hypertensive transgenic (mRen-2)27 homozygous and heterozygous rats, which overexpress renin and angiotensin in extrarenal tissues, reported that AT1R expression is reduced in (mRen-2)27 homozygous rats, and this decrease may be a result of elevated levels of Ang II in this strain compared with (mRen-2)27 heterozygous rats [34]. In addition, high levels of Ang II downregulate Ang II receptors in rat cultured granulosa cells [35] and aortic vascular smooth muscle cells [36].…”
Section: Discussionmentioning
confidence: 84%